Realizacja woli spadkodawcy a postępowanie działowe - Studzińska, Joanna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The most important function of the partition of inheritance is the realization of socio-economic objectives that the law system assigns the institution of succession. Above all the main aim of this procedure is to obtain exclusive rights to the designated assets of the estate by individual heirs. But it is important to respect the will of the testator, who left a fortune downward. It is reasonable to examine the extent to respect the will of the testator during the partitioning procedure, as far as the law decides about it and whether regulations on this matter are adequate. It also seemed significant to study whether it is important to respect the interests of heirs including the real will of the testator
Keywords: testator’s will; proceedings for inheritance; regulatory restrictions of inheritance